Development of Comics Media to Improve Science Literacy and Concepts Understanding Junior High School Students In Central Halmahera Regency Through Reading Literacy Program - Ade, Risnawati; Nasichah , Arini Z.; Mas'ud, Abdu (Jurnal Pijar Mipa, 2025)
In the era of globalization and information technology that continues to develop, the world of education must be able to adapt to various changes. One very important aspect of the world of education is the use of learning media. This study aims to determine whether the development of learning media in the form of comics based on scientific literacy and students' conceptual understanding developed in this study is suitable for use in the learning process at SMP Negeri 4 Halmahera Tengah through the reading literacy program and to determine whether learning media in the form of comics can improve scientific literacy and students' conceptual understanding at SMP Negeri 4 Halmahera Tengah through the reading literacy program. This research is a type of development research (Research and Development). The data collection technique used in this study is to use five stages, namely the Define Stage, Development Stage, Interview, Observation, and Response Questionnaire. The study's data sources are divided into two parts, namely qualitative and quantitative data. Data analysis techniques in the study used the One-Group Pretest-Posttest Design, T-Test, and N-Gain Test. The study results showed that: 1) Regarding validity, the total percentage of the average value of media and material experts was 96%, categorized as "Very Valid." 2) Practicality is obtained by the total average percentage value of small-scale student responses, resulting in a score of 96%, which is categorized as "Very Practical." 3) Effectiveness is obtained from the T-test with Sig. 0.000, where <0.05 indicates a difference in students' scientific literacy and conceptual understanding before and after using comic media on the material of plant and animal reproductive systems. The N-Gain test obtained an average percentage score of 0.65, categorized as "Moderate." Based on these three results, it can be concluded that the development of comic media to improve scientific literacy and conceptual understanding of junior high school students in Central Halmahera Regency through the reading literacy program can be said to be feasible to be used to improve scientific literacy and conceptual understanding.